Active Bone Conduction Prosthesis: BonebridgeTM - Zernotti,Mario E. (2015)
Introduction Bone conduction implants are indicated for patients with conductive and mixed hearing loss, as well as for patients with single-sided deafness (SSD). The transcutaneous technology avoids several complications of the percutaneous bone conduction implants including skin reaction, skin growth over the abutment, and wound infection. The Bonebridge (MED-EL, Austria) prosthesis is a semi-implantable hearing system: the BCI (Bone Conduction Implant) is the implantable part that contains the Bone Conduction-Floating Mass Transducer (BC-FMT), which applies the vibrations directly to the bone; the external component is the audio processor Amadé BB (MED-EL, Austria), which digitally processes the sound and sends the information through the coil to the internal part. Bonebridge may be implanted through three different approaches: the transmastoid, the retrosigmoid, or the middle fossa approach. Objective This systematic review aims to describe the world́ s first active bone conduction implant system, Bonebridge, as well as describe the surgical techniques in the three possible approaches, showing results from implant centers in the world in terms of functional gain, speech reception thresholds and word recognition scores. Data Synthesis The authors searched the MEDLINE database using the key term Bonebridge. They selected only five publications to include in this systematic review. The review analyzes 20 patients that received Bonebridge implants with different approaches and pathologies. Conclusion Bonebridge is a solution for patients with conductive/mixed hearing loss and SSD with different surgical approaches, depending on their anatomy. The system imparts fewer complications than percutaneous bone conduction implants and shows proven benefits in speech discrimination and functional gain.